RELASI MAQASHID SYARIAH DAN INTERAKSI SOSIAL DI MASYARAKAT PESANTREN - Wahyu Fitrianoor; Ahmad Fauzan Arifin (AL-FALAH: Jurnal Keislaman dan Kemasyarakatan, 2026)
This study aims to analyze the relationship between maqāṣid al-sharī‘ah and social interaction within the pesantren community in Banjarbaru, South Kalimantan, from the perspective of Islamic sociology of law. The research employs an empirical qualitative approach through field observation, in-depth interviews, and document analysis. The findings indicate that the principles of protecting religion (ḥifẓ al-dīn), life (ḥifẓ al-nafs), intellect (ḥifẓ al-‘aql), lineage (ḥifẓ al-nasl), and property (ḥifẓ al-māl) are internalized within the social structure of the pesantren. The authority of the kiai, the educational system, dormitory regulations, and the tradition of deliberation reflect the operationalization of maqāṣid as a living norm (living law) that fosters social cohesion and community stability. The moral and ethical development of students is shaped through value habituation, exemplary leadership, and moral legitimacy rather than coercive dominance. Furthermore, the hierarchical structure of the pesantren cannot be reduced to modern feudalism; instead, it functions as a pedagogical and integrative mechanism that maintains social balance. This study contributes to strengthening maqāṣid al-sharī‘ah as an analytical paradigm of social praxis and enriches the discourse of Islamic sociology of law within contemporary pesantren communities.